FATAL AORTIC ANEURYSM RUPTURE SECONDARY TO SPIROCERCOSIS: A CASE REPORT - K. B. Jyothi; M. Mounika; G. Anusha (The Indian Veterinary Journal, 2026)
Canine spirocercosis, caused by the nematode Spirocerca lupi, is a clinically significant parasitic disease of carnivores in tropical and subtropical regions. This report describes a fatal case of aortic aneurysm rupture in a four-year-old non-descript dog presenting with exercise intolerance. Post-mortem examination revealed hemothorax, pale mucous membranes, and aortic aneurysm with rupture containing adult worms. Histopathological examination of the aorta demonstrated worm-filled tunnels, extensive necrosis, inflammatory infiltration, and fibrosis. Death was attributed to hypovolemic shock secondary to S. lupi-induced vascular deterioration. This case highlights the importance of early diagnosis in endemic areas